Biomechanics of wheelchair turning manoeuvres: novel insights into wheelchair propulsion - Chaikhot, Dhissanuvach; Taylor, Matthew J. D.; de Vries, W. H. K.; Hettinga, Florentina J. (Frontiers in Sports and Active Living, 2023)
Introduction: Wheelchair turning biomechanics has been largely neglected despite its obvious relevance to functional mobility of wheelchair users. Wheelchair turns might be linked to a higher risk of upper limb injuries due to the increased forces and torques potentially associated with asymmetric movement. Our aim was to obtain better theoretical understanding of wheelchair turning by biomechanically analyzing turns compared to straight line propulsion (SL). Methods: Ten able-bodied men received 12-min familiarization and 10 trials (in a random order) of SL and multiple left and right turns around a rectangular course. A Smartwheel was mounted at the right wheel of a standard wheelchair to measure kinetic parameters during SL and of the inner hand during right turns and the outer hand during left turns. A repeated measures ANOVA was used to detect differences across tasks (p < 0.05). Results: Two strategies were identified: 3% demonstrated roll turns and 97% spin turns. Spin turns consisted of three phases: approach, turning and depart phase. Turning phase was accomplished by increasing peak force (72.9±25.1N vs. 43.38±15.9N in SL) of the inner hand, while maintaining high push frequency of the outer hand (1.09±0.20push/s vs. 0.95 ± 0.13push/s in SL). Peak force and force impulse during turning phase were much higher than SL, 1.9±0.8 and 4.5±1.7 times higher, respectively. Conclusion: The spin turn strategy might carry an increased risk of upper limb injuries due to higher braking force and requires particular attention by rehabilitation professionals to preserve upper limb function of long-term wheelchair users.